Development of PAMAM dendrimer-modified magnetic polyoxometalate: A novel platform to reinforce mechanical and thermal properties of diglycidyl ether of bisphenol A/isophorone diamine hardener epoxy. (September 2022) - Maleki, Behrooz; Jafari-Soghieh, Fariba; Alinezhad, Heshmatollah; Ghani, Milad; Ali jamshidi,
The present study explores the mechanical and thermal properties of DGEBA/IPD epoxy reinforced with dendrimer-functionalized magnetitepolyoxometalate nanoparticles. Magnetic iron oxide nanoparticles (MNP's) were stabilized and functionalized by the poly (amido-amine) dendrimer via encapsulation within dendrimer; afterwards, H9 [α-P2 V3 W15 O62 ] polyoxometalate (POM) was modified with dendrimer-functionalized magnetic iron oxide nanoparticles (DMNP's). The polyoxometalate can be complexed with DMNP's via protonation of dendrimer amino groups. In the next step, dendrimer-functionalized magnetitepolyoxometalate nanoparticles (DMNP's-POM) were loaded into diglycidyl ether of bisphenol A (DGEBA) epoxy resin. The DMNP's-POM nanoparticles can initiate polymerizations of epoxy resin with isophorone diamine hardener (IPD); on the other hand, the terminal amino groups of the dendrimer in the DMNP's-POM nanoparticles allow them to be covalently linked to the polymer matrix alongside the main amine hardener. The resulting epoxy/magnetitepolyoxometalate nanocomposites (DMNP's-POM@EN 5%) are thoroughly characterized by FT-IR, FE-SEM, and XRD analysis. Probing thermal behaviors of epoxy/magnetitepolyoxometalate nanocomposites by TGA reveals that the resulting composites are degraded thermally through a simple one-step process with an initial degradation close to 340°C, and show significant stability toward heat. Dynamic Mechanical Thermal Analysis indicates that no considerable agglomerate is formed during the synthesis process, and the incorporated nanoparticles somewhat limit the segmental motions of the epoxy macromolecular chains.